2006
DOI: 10.1007/s00299-006-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive expression analysis of the WRKY gene superfamily in rice plants during defense response

Abstract: To understand the transcriptional regulatory mechanism of host genes during the activation of defense responses in rice, we isolated WRKY transcription factors whose expressions were altered upon attack of the fungal pathogen Magnaporthe grisea, the causal agent of the devastating rice blast disease. A systematic expression analysis of OsWRKYs (Oryza sativa L. WRKYs) revealed that among 45 tested genes the expression of 15 genes was increased remarkably in an incompatible interaction between rice and M. grisea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
192
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(205 citation statements)
references
References 67 publications
9
192
1
3
Order By: Relevance
“…The rice genome contains more than 100 WRKY genes, often present in duplicated chromosomal regions, suggesting genome duplications as one of the mechanisms for the expansion of this family in this plant species (Ross et al, 2007;Ramamoorthy et al, 2008). The majority of these genes respond to (a)biotic stresses and various phytohormones (Ryu et al, 2006;Ramamoorthy et al, 2008). Individual WRKY members have been associated with pathogen defense, albeit with the caveat that the majority of such studies have employed strong ecotopic overexpressor lines.…”
Section: Recent Developments In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…The rice genome contains more than 100 WRKY genes, often present in duplicated chromosomal regions, suggesting genome duplications as one of the mechanisms for the expansion of this family in this plant species (Ross et al, 2007;Ramamoorthy et al, 2008). The majority of these genes respond to (a)biotic stresses and various phytohormones (Ryu et al, 2006;Ramamoorthy et al, 2008). Individual WRKY members have been associated with pathogen defense, albeit with the caveat that the majority of such studies have employed strong ecotopic overexpressor lines.…”
Section: Recent Developments In Ricementioning
confidence: 99%
“…JA and SA signaling usually act antagonistically, but synergism between these two phytohormones has also been observed (Mur et al, 2006). These responses to pathogen attack require large-scale transcriptional reprogramming, including those of TF families such as WRKY genes (Eulgem, 2005;Ryu et al, 2006;Naoumkina et al, 2008).…”
Section: Wrky Factors In Disease Resistance Networkmentioning
confidence: 99%
“…Plant immune responses are associated with the concerted modulation of a large number of different WRKY transcripts and proteins [15,[34][35][36]37 ]. Upon triggering of SAdependent defenses, at least 49 AtWRKY genes exhibited differential regulation representing separate waves of transcript accumulation or repression [34].…”
Section: The Wrky Webmentioning
confidence: 99%
“…7,8) The rice genome is predicted to contain over 100 WRKY (OsWRKY) genes. 9) It has been found that several WRKY genes are expressed in response to the rice blast fungal elicitor 10) and the defense signal molecules salicylic acid and jasmonic acid, 11) and that OsWRKY13 and OsWRKY45 are involved in salicylic acid-mediated defense signaling in rice, 12,13) but the biological functions of most of the WRKY factors in defense signaling in rice remain unknown.…”
mentioning
confidence: 99%